RARE-09. PRESERVATION OF ENDOCRINE FUNCTION AFTER OMMAYA RESERVOIR INSERTION IN CHILDREN WITH CYSTIC CRANIOPHARYNGIOMA. (4th December 2020) - Lohkamp, Laura-Nanna; Kulkarni, Abhaya; Drake, James; Rutka, James T; Dirks, Peter; Taylor, Michael; Ibrahim, George; Baroni, Lorena; Hamilton, Jill; Bartels, Ute Katharina
Abstract: INTRODUCTION: Children with craniopharyngiomas (CP) can be subjected to significant morbidities caused by radical surgery and/or radiation with severe long-term consequences. Ommaya reservoir Insertion (ORI) into cystic CP represents a minimally invasive procedure that aims to preserve endocrine, hypothalamic and neurocognitive function. The purpose of this study was to determine the relevance of upfront ORI (+/- intracystic treatment) for preservation of endocrine function. METHODS: A retrospective chart review of children with CP treated at the Hospital for Sick Children between 01/01/2000 and 15/01/2020 was undertaken. Endocrine function was reviewed at the time of initial ORI or surgical resection and throughout the course of follow-up. Event free survival (EFS) was defined as the time to additional surgical resection or irradiation. RESULTS: Fifty-five patients with sufficient endocrine follow-up data were included. The median age of diagnosis was 8.3 years (range 2.1–18.0 years), 31 were males. ORI was performed as upfront treatment in 30 patients, gross total or partial resection in 24 patients and radiation in 1 patient, respectively. Endocrine function remained stable after ORI with a median EFS of 19.2 (0 – 105.3) months while the majority of patients who underwent surgical resection had documented worsened endocrine function postoperatively (median of 0; range 0 – 29.4 months) (p< 0.001). The event most commonly related to secondary endocrine deterioration was initial or delayed surgical resection. CONCLUSIONS: Endocrine function was preserved in patients with upfront ORI (+/- intracystic treatment). Further studies will elucidate the implications of ORI with respect to ophthalmological, vascular and neurocognitive long-term outcome.